2013
DOI: 10.7241/ourd.20133.72
|View full text |Cite
|
Sign up to set email alerts
|

What factors contribute to a higher frequency of skin infections among adults in Mauritius?

Abstract: Introduction: Given the rise in the prevalence of skin infections in many countries and the lack of published data pertaining to the prevalence and awareness of skin infection in Mauritius, this survey is the first of its kind to provide data on this issue. The aim of this study is to describe the association of skin infection with various predisposing factors such as socioeconomic status, personal hygiene and level of awareness and to assess the impact of skin infections on quality of life. Material and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…226,227 Lack of awareness of risk factors contributes significantly to the development of mycotic skin infections. 228 In developing countries, these infections may get transmitted from one person to another by sharing common household things and fomites (hat, comb, scarf, etc) as well as due to overcrowded human settings. 229 This has been further supported by one of the studies where contact was observed to be a possible source of infection in 48% of studied cases, whereas trauma contributed to 23%.…”
Section: Ris K Fac Tor S and Mode Of Tr An S Miss I On Of Superfi Cial Mycos E Smentioning
confidence: 99%
See 1 more Smart Citation
“…226,227 Lack of awareness of risk factors contributes significantly to the development of mycotic skin infections. 228 In developing countries, these infections may get transmitted from one person to another by sharing common household things and fomites (hat, comb, scarf, etc) as well as due to overcrowded human settings. 229 This has been further supported by one of the studies where contact was observed to be a possible source of infection in 48% of studied cases, whereas trauma contributed to 23%.…”
Section: Ris K Fac Tor S and Mode Of Tr An S Miss I On Of Superfi Cial Mycos E Smentioning
confidence: 99%
“…The major risk factors responsible for the high frequency of superficial mycosis include age, underlying diseases, suppressed immunity and obesity 226,227 . Lack of awareness of risk factors contributes significantly to the development of mycotic skin infections 228 . In developing countries, these infections may get transmitted from one person to another by sharing common household things and fomites (hat, comb, scarf, etc) as well as due to overcrowded human settings 229 .…”
Section: Risk Factors and Mode Of Transmission Of Superficial Mycosesmentioning
confidence: 99%
“…The skin infection has a high prevalence rate which reaches up to 80 % in developing countries (Ramamuthie et al, 2015). Lack of awareness and understanding of risk factors for skin infection is a major reason for the development of skin infections (Goonmatee and Rajesh, 2013). The skin works as a mechanical barrier which limits the invasion and growth of pathogenic fungi (Harder et al, 1997).…”
Section: Skin Infectionsmentioning
confidence: 99%